Welfare regime and labour migration policy for elderly care: new phase of social development in Taiwan. Issue 3 (2nd October 2017) - Asato, Wako
Abstract: Unique aspect of elder care in Taiwan is the existence of large number of migrant care workers in the informal labour market before the formation of universal welfare provision. The migrants were introduced in the 1990s, as part of the labour policy to increase more women into the labour market. The democratisation has led to the expansion of welfare state but the issue of labour migration and the human rights of the migrants were set aside. Although migrants share proportionate amount of care work, they are segregated in the informal labour market. The paper examines the recent developments in Taiwan's welfare state, including its effort to formalise care, and highlight the issue of migrant care workers within the familialistic welfare regime.